2019
DOI: 10.1007/s11126-019-09657-w
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for Emergency Department Use among Patients with Mental Disorders

Abstract: Disproportionate use of emergency departments (EDs) by patients with mental disorders3 suggests the need to evaluate factors associated with ED use. Based on the Andersen 4 Behavioral model, this mixed-method study identified the contributions of predisposing, 5 enabling and needs factors in ED use among 328 patients with mental disorders. We 6 hypothesised that ED use for mental health (MH) reasons would be most strongly 7 associated with need factors. The study was conducted in four EDs located in different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 49 publications
1
24
0
Order By: Relevance
“…Despite previous negative encounters, young people in this study described the ED as being the only option available for help with suicidal thoughts and behaviours. Other studies have found that the ED was seen as the only available choice for individuals with mental health concerns including suicidal behaviour, self-harm, substance misuse, anxiety and depression [52][53][54]. Alternatives to presenting to the ED for young people needs to be further explored to assist with reducing negative experiences and promoting help-seeking behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Despite previous negative encounters, young people in this study described the ED as being the only option available for help with suicidal thoughts and behaviours. Other studies have found that the ED was seen as the only available choice for individuals with mental health concerns including suicidal behaviour, self-harm, substance misuse, anxiety and depression [52][53][54]. Alternatives to presenting to the ED for young people needs to be further explored to assist with reducing negative experiences and promoting help-seeking behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative studies conducted overseas (Fleury et al . 2019; Vandyk et al . 2019; Wise‐Harris et al 2017; Clarke et al .…”
Section: Introductionmentioning
confidence: 99%
“…Although recent studies highlight the increasing demand on ED services by those with NFSB, there is limited literature on how consumers with NFSB describe their ED experience and the interventions provided. Qualitative studies conducted overseas (Fleury et al 2019;Vandyk et al 2019;Wise-Harris et al 2017;Clarke et al 2007) and in Australia (Morphet et al 2012) have focused on the perceptions of the ED by the broader mental health population. Findings from these studies may not be specific to those with NFSB.…”
Section: Introductionmentioning
confidence: 99%
“…Persons who frequently visit PES have been shown to have complex and multifaceted needs (cf. Fleury, Grenier, Farand, & Ferland, 2019;Schmidt et al, 2018b), some of which may remain unmet if people have difficulties expressing them in the first place. Compounding this challenge may be the fact that persons who frequently visit PES are a heterogeneous group that varies greatly in diagnostic profile, socioeconomic characteristics, and temporal utilization patterns (Schmidt et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%